Determinants of profitability of commercial bank a case study of CIMB Bank in Malaysia / Muhammad Rauf Mohd Roslan - Mohd Roslan, Muhammad Rauf (Faculty of Business and Management, 2019)
This study examines the factors affecting the profitability of CIMB Bank in Malaysia with four variables where is Consumer Price Index (CPI), Deposit (DEP), Gross Domestic Product (GDP) and Loan Loss Provision (LLP). This research employs annually times series data throughout the timeline 1989 until 2018 with total 30 data observations and all the variables are test by using the statistical software Eviews 10 package. This study is used Ordinary Least Square (OLS) method to obtain the results. This study used Return on Asset (ROA) as an indicator for measured profitability. Meanwhile, the results revealed the consumer price index and gross domestic product have insignificant relationship on profitability of CIMB Bank in Malaysia. Next, deposit has significant positive relationship with profitability of CIMB Bank. In addition, loan loss provision show has significant negative relationship with profitability of CIMB Bank. The findings could provide some guidance to future researcher in monitoring the profitability of CIMB Bank in Malaysia.